Producing Precipitated Calcium Carbonate (PCC) from CO2 Emissions during OFMSW Bio-Drying through Carbonation: A Preliminary Study - Eko Naryono; Cucuk Evi Lusiani; Mochammad Agung Indra Iswara; Abdul Chalim; Noor Isnaini Azkiya; Amalia Dwi Ardini Putri; Allivia Retnaning Tyas; Kaliawan Kaliawan (Jurnal Teknik Kimia dan Lingkungan, 2026)
Capturing CO₂ emissions during the bio-drying process of organic fraction municipal solid waste (OFMSW) presents an alternative approach to reducing CO₂ emissions in municipal solid waste (MSW) management. Absorption using an aqueous solution of Ca(OH)₂ is a viable CO₂ capture technology that produces precipitated calcium carbonate (PCC), a value-added product. The objectives of this study are to assess the impact of bio-drying aeration flow rate and absorption time in the Ca(OH)₂ solution on CO₂ absorption efficiency, the conversion of Ca(OH)₂, and the mass of the PCC product. The absorption process was performed in a semi-continuous bubble reactor with 15 L of 0.019 M Ca(OH)₂ aqueous solution. At bio-drying aeration flow rates of 5.1, 4.6, and 3.9 L/min/kg of waste, with CO₂ concentrations ranging from 1286 to 4395 ppm and temperatures between 23 to 30°C over a bio-drying period of 96 hours, it was observed that higher flow rates resulted in lower conversion rates of Ca(OH)₂ and reduced CO₂ absorption efficiency. The highest recorded conversion rates for Ca(OH)₂ and CO₂ absorption were 97.3% and 16.4%, respectively, yielding a PCC product of 4.8 g/kg of waste at an aeration flow rate of 3.9 L/min/kg waste and an absorption duration of 48 hours. FTIR and SEM analysis confirmed the presence of both calcite and aragonite crystal forms in the PCC product, as well as hydrated CaCO₃.